Global currency hierarchy and national policy space: a framework for peripheral economies - Barbara Fritz; Luiz Fernando de Paula; Daniela Prates (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
In this paper, we develop a Keynesian–structuralist perspective on the origins and implications of the currency hierarchy in the international monetary and financial system. We show that international asymmetry in monetary affairs results in structural implications for peripheral economies. Our main hypothesis is that the international asymmetry related to the currency hierarchy, amplified by financial globalization, imposes major constraints on the adoption of Keynesian policies in these economies. These vary over time and space and depend on certain structures, such as the specific global monetary regime, as well as on domestic institutions and policy variables. For this purpose, we first develop the concept of currency hierarchy and then discuss the structural policy space limitations for the countries at the bottom of this hierarchy. Finally, we provide some brief reflections on the challenges connected to climbing this hierarchy.
Keywords: F3; F4; E6; 330; financial globalization; currency hierarchy; Keynesian policies